(untitled) (Journal of Bio-Science, 2009)
Oil was extracted from Terminalia belerica Roxb. seed kernel by solvent extraction process. The whole seed contained 12.28 % oil on dry basis. The physico-chemical properties of the oil were determined. Moisture, ash and crude fibre contents of the seed kernel were found to be 8. 43, 2.54, and 8.78% respectively. The refractive index, co-efficient of viscosity, specific gravity, and energy of activation of the oil were found to be 1.28, 403.6 millipoise at 30Â°C, 0.93 and 6.97 k.cal/mole respectively. The oil was found to be non-drying. Iodine value, acid value, peroxide value, saponification value, saponification equivalent, ester value, unsaponifiable matter, acetyl value, Reichert-Meissel value, Polenske value, free fatty acids as oleic acid and cholesterol content of the oil were recorded as 107, 3.69, 3.14, 189.24, 296.44, 185.55, 1.24%, 3.78, 0.719, 0.945, 0.87% and 26.59 mg per 100 g oil, respectively. The oil was qualitative and quantitative analysed for fatty acid composition by TLC and GLC. The results showed that the fatty acids of the oil had chain length between C14 to C22. The oil contained 17.70% myristic acid, 21.6% palmitic acid, 45.67% oleic acid and 14.93% stearic acid. The whole kernel was analyzed for some nutrients and minerals. The kernel contained 22.57 and 8.38% total lipid and protein respectively. It also contained 0.19mg, 0.45mg, 0.79g and 1.1mg of vitamin B1, B2, C and A respectively per 100g of kernel. Ca, Mg, K, Na, P, Fe, Mn, Zn and Cu were found to be 0.3, 0.02, 0.2, 0.2, 0.01%; 23, 1, 12 and 12 ppm respectively in kernel and 0.12, 0.05, 1.15, 0.18, 0.45%; 204, 4, 54 and 50 ppm respectively in oil. Key words: T. belerica seed oil and kernel, physico-chemical behaviour, micronutrients, fatty acid profile, GLC. Â doi: 10.3329/jbs.v15i0.2211 Â J. bio-sci. 15: 117-126, 2007